On the cost of delayed currency fixing announcements - Christoph Becker; Uwe Wystup (HfB - Business School of Finance & Management, Centre for Practical Quantitative Finance (CPQF), 2005)
In Foreign Exchange Markets vanilla and barrier options are traded frequently. The market standard is a cutoff time of 10:00 a.m. in New York for the strike of vanillas and a knock-out event based on a continuously observed barrier in the inter bank market. However, many clients, particularly from Italy, prefer the cutoff and knock-out event to be based on the fixing published by the European Central Bank on the Reuters Page ECB37. These barrier options are called discretely monitored barrier options. While these options can be priced in several models by various techniques, the ECB source of the fixing causes two problems. First of all, it is not tradable, and secondly it is published with a delay of about 10 - 20 minutes. We examine here the effect of these problems on the hedge of those options and consequently suggest a cost based on the additional uncertainty encountered.
Keywords: C15; G12; 330; exotic options; currency fixings; Optionspreistheorie; Simulation; Capital Asset Pricing Model; Theorie